Legitimidade da jurisdição constitucional para realizar o controle concentrado material da moralidade política - Oliveira, José Flávio Fonseca de (2021)
The objective of this dissertation is to address the legitimacy of constitutional jurisdiction to make concentrated control of material constitutionality of laws or normative acts that confront political morality. The method used was the hypothetical-deductive method based on bibliographic research of the main authors on the legitimacy of constitutionality control in topics of political morality. It starts with the theoretical framework of Ronald Dworkin who approaches political morality as the set of the political community’s moral principles, when translating the feeling of collective justice, provides the best interpretation of how the citizen should act in society, and in the name of society, and it is directly related to the fundamental rights. The main hypothesis is that it is not up to the Supreme Court to carry out the concentrated control of material constitutionality when the law or normative act affronts political morality because this function must be exercised by the Legislator, whose legislative process’s outcome must be limited to respect for fundamental rights. This study is justified due to the expansion of constitutional jurisdiction in several countries around the world, a movement that also occurs in Brazil in matters of political morality. The dissertation presents three chapters and in the first one the concepts of political morality, public morality and public opinion are presented, as well as the response to which political morality is inserted in fundamental rights. The following chapter presents the characteristics of constitutionality control, the concepts of constitutionality parameter and constitutionality “block” and, at the end, there is a debate about political integrity of the Legislative and Judiciary in order to answer whether political morality can be a parameter of constitutionality control. The last chapter presents the substantial limits and procedural parameters that make the decisionmaking process more democratic and more deliberative. It advocates the adoption of a Deliberative Court, the opening of the constitutional interpretation to all interested parties, as well as the institutional dialogue between the three branches in matters of political morality. The study’s conclusion in the last guardian idea should be abandoned, to privilege the division of constitutional functions in which each branch of government decides on issues of political morality in permanent dialogue with each other and with the direct or indirect participation of those involved and thereby materializing the rights of all.